(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
Infrastructure as Code (IaC) has become the dominant paradigm for provisioning and managing cloud infrastructure at scale. Tools such as Terraform enable declarative, repeatable infrastructure deployments across heterogeneous cloud environments. However, as organizations adopt Terraform for managing large-scale, multi-cloud estates, they encounter systemic operational challenges that extend beyond infrastructure provisioning. These challenges include uncontrolled configuration drift, inconsistent governance enforcement, high change failure rates, and growing cognitive load on platform and SRE teams. This paper introduces a Policy-Driven Infrastructure Lifecycle Control Plane for Terraform-based multi-cloud environments. The proposed control plane elevates Terraform from a deployment tool to a governed execution engine within a broader lifecycle management system. Unlike existing approaches that focus on static policy checks during plan or apply phases, the control plane enforces governance continuously across the entire infrastructure lifecycle—pre-deployment, deployment-time, and post-deployment runtime. The framework integrates policy evaluation, state reasoning, drift detection, risk-aware change control, and human-in-the-loop approvals into a unified architecture. By decoupling governance logic from Terraform configurations and embedding policy enforcement throughout the infrastructure lifecycle, the control plane addresses fundamental limitations of current IaC practices. The proposed approach improves operational safety, reduces configuration drift, and enhances compliance consistency across multi-cloud environments while preserving developer velocity.